The reality of using electronic calendar in secondary school in Al- Ahsa Governorate in light of the Corona pandemic from the point of view of teachers and students - Alsayafi, Ali Abdulaziz (Journal of Educational and Psychological Sciences, 2022)
The study aimed to identify the reality of using the electronic calendar in the secondary stage of the Mubarraz Education Office in Al- Ahsa Governorate in light of the Corona pandemic from the point of view of teachers and students. Teaching Mubarraz in the academic year (1442 AH), who taught during the period of the Corona pandemic through distance education, and the necessary data was collected using a questionnaire consisting of (40) phrases distributed over four areas, and the results showed that the reality of teachers’ use of electronic evaluation came with a degree of (Agree, with a mean of (3.77), and a percentage of (73.9%), and that the high school students’ satisfaction with the use of the electronic calendar came with a degree of (Agree), and the arithmetic average was (3.99) and a percentage of (80%), and there were obstacles The use of electronic assessment from the teachers’ point of view with a degree (agree) and an arithmetic average of (3.42), and a percentage of (68.4%), while the obstacles to using electronic assessment came from the students’ point of view with a degree (agree) and an arithmetic average of (3.4), and a percentage of (68%), The study recommended the necessity of providing an appropriate structure for applying electronic assessment in secondary schools, training teachers on electronic assessment tools and procedures, and adopting creative initiatives in the field of electronic assessment.
Keywords: electronic calendar; distance education; corona virus; secondary school